The Economic Information Resource and its Distribution - Brazaitis, Zenonas (Ekonomika, 1996)
First, we examine users’ informational requirements for economic object control and their definition with respect to the object condition. The variables and parameters of information system are classed. Next, we present a model for distribution of the information resource. It is based on the well-known Th. Bayes principle. The use of the useful effect and alternative expenditures matrixes are described. The main contribution or this paper is an algorithm for the search of the optimum version to content informational requirements. This algorithm is amenable to concrete adaptation.